Polarographic Investigation of Binary and Ternary Pd(II) Complexes with L-2-Amino-3-(4-Hydroxy Phenyl) Propanoic Acid, 2,2´ -Bipyridine and 1,10-Phenanthroline - Bapna, R.K.; Gupta, K.D.; Saxena, K.K. (Asian Journal of Chemistry, 2010)
Polarographic study of simple and mixed Pd(II) complexes with L-2-amino-3-(4-hydroxy phenyl) propanoic acid, 2,2´-bipyridine and 7,10-phenanthroline reveals that the reduction of these complexes involves two electron transfer, irreversible and diffusion controlled steps. The formal rate constants (Kºf,h) and the transfer coefficient (αn) are determined by Koutecky's method as extended by Meites and Isreal. Theromodynamic parameters have also been evaluated.